Dictionary of law - Collin, P. H. (Peter Hodgson). (London : A. & C. Black, 2007)
With over 8,000 terms and expressions, provides clear, concise and fully up-to-date information on all aspects of civil, criminal and commercial law. Examples and encyclopedic comments help to explain complex terms from British, European and US legal procedure.
Previous ed.: published by Peter Collin, London: Bloomsbury, 2004.
Includes graphical cross-reference mapper.
Keywords: Law -- Dictionaries